The Role of PPID in Implementing Policy, Service, Publication of Public Information in State University of Medan - M. Surip; M. Oky Fardian Gafari; Hendra K. Pulungan (BIRCU, 2020)
The Information and Documentation Management Officer (PPID) at State University of Medan was formed to answer the Minister of Research and Technology Regulation No. 75 of 2016 concerning Public Information Services in the Ministry of Research, Technology and Higher Education. In carrying out its duties as a provider, store, document, and safeguard public information, PPID synergizes with the Cooperation and Public Relations Subdivision which routinely publishes all information through the State University of Medan official website and social media immediately. This research was conducted with the aim of analyzing the role of PPID in carrying out the task of implementing policies, services, and public information publications at Medan State University, as well as analyzing the obstacles encountered and providing solutions to efforts to overcome these obstacles. The method used in this research is descriptive research method. The results showed that based on observations made, it was obtained that more than 70 percent of respondents concluded that they were very satisfied with the public information services provided so far. 2. There are three main substances of the KIP laws and regulations that are used as the main reference for determining the assessment parameters that will be used as an assessment instrument. First, fulfillment of the obligation on information that must be provided and announced periodically in accordance with Article 9 of the FOI Law, which is more detailed in Article 11 of the Information Commission Regulation Number 1 of 2010 concerning Public Information Service Standards (SLIP). The review of information that must be made available and announced periodically is done by means of publication in the form of the main website of the Public Agency with instruments to fulfill the points as stipulated in the KIP laws and regulations. 3. The efforts made by PPID State University of Medan are in overcoming the obstacles faced are: a) Provision of information, b) Information services that are fast, accurate, and simple, in accordance with applicable regulations, c) Determination of operational procedures for disseminating public information, d) Testing of consequences, d) Classification of information, e) Determination of excluded information that has expired, f) Determination of consideration for each policy taken to fulfill the right of everyone to public information.